Cultural aspects of pedagogical acmeology - Ayagan, Y.S.; Zhekibayeva, B.A.; Aubakirova, K.F.; Utebayev, I.S.; Kipshakov, S.A. (Int. J. Learning and Change, 2021)
The relevance of the study is that the educational acmeology is very important in the process of the professional development of teachers. The purpose of the article is to consider pedagogical acmeology as the science of how to achieve professionalism and competence in the work of the teacher. It was reflected the preliminary results of the research work of acmeology of general and professional education. The results of a study of pedagogical acmeology are presented in two directions: cultural aspects of pedagogical acmeology and integrative communication of pedagogical acmeology. Recourse to unresolved and controversial issues of pedagogical acmeology allows the representatives of different scientific areas to broaden the horizons of scientific fields – perhaps the development of ecolinguistic, econoosphere pedagogics and acmeology of management and many others.
Keywords: self-knowledge; self-regulation; self-realisation; competence; functionalism; humanism